2015
DOI: 10.24246/j.scholaria.2015.v5.i2.p131-149
|View full text |Cite
|
Sign up to set email alerts
|

Pengimplementasian Media Pembelajaran Berbasis Multimedia Interaktif Pada Mata Pelajaran Matematika Di Sekolah Dasar

Abstract: ABSTRAKKurangnya minat siswa dalam mempelajari matematika disebabkan karena pendekatan pembelajaran yang digunakan guru masih konvensional sehingga menyebabkan siswa tidak tertarik untuk mempelajari matematika. Penelitian ini bertujuan untuk mengetahui bagaimana media pembelajaran berbasis multimedia interaktif dapat mempengaruhi minat belajar. Penelitian ini menggunakan desain quasi eksperimen nonequivalent control group. Hasil penelitian diperoleh peningkatan aspek minat belajar siswa pada mata pelajaran mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
24

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 2 publications
1
4
0
24
Order By: Relevance
“…Involving students as the learning targets in the use of mathematics interactive multimedia was also proven by the result of questionnaire distributed to students which focused on the instrument items related to the use of interactive multimedia in mathematics learning which was very interesting and gave convenience for the students to understand the material obtained (94%) with very good criteria in individual trials, and very good criteria (93.33%) in small group trials. Thus, it can be concluded that mathematics interactive multimedia can trigger the interest and involvement of learning objectives and help the students to master the material, this is in line with the results of a research conducted by [23] that the use of interactive multimedia in mathematics learning provided an interesting experience for students that encouraged them to be actively involved in the learning process. [24] added that interactive multimedia which was designed for mathematics learning can provide convenience for students to learn the use of images, sounds, and animation as well as supported the learning process to be effective in involving the students to learn actively.…”
Section: Discussionsupporting
confidence: 81%
“…Involving students as the learning targets in the use of mathematics interactive multimedia was also proven by the result of questionnaire distributed to students which focused on the instrument items related to the use of interactive multimedia in mathematics learning which was very interesting and gave convenience for the students to understand the material obtained (94%) with very good criteria in individual trials, and very good criteria (93.33%) in small group trials. Thus, it can be concluded that mathematics interactive multimedia can trigger the interest and involvement of learning objectives and help the students to master the material, this is in line with the results of a research conducted by [23] that the use of interactive multimedia in mathematics learning provided an interesting experience for students that encouraged them to be actively involved in the learning process. [24] added that interactive multimedia which was designed for mathematics learning can provide convenience for students to learn the use of images, sounds, and animation as well as supported the learning process to be effective in involving the students to learn actively.…”
Section: Discussionsupporting
confidence: 81%
“…Berdasarkan sudut pandang siswa, kelebihan media pembelajaran digital adalah dapat meningkatkan pemahaman konsep matematis siswa (Nurdin et al, 2019) sekaligus meminimalkan munculnya miskonsepsi (Loong, 2014) karena media pembelajaran digital juga dapat memuat banyak contoh-contoh terkait suatu konsep. Dampaknya, media ini juga mampu meningkatkan hasil belajar siswa (Lagrange & Kynigos, 2014;Moyer-Packenham & Westenskow, 2013;Nurdin et al, 2019;Paseleng & Arfiyani, 2015). Selain itu, penggunaan media ini dapat meningkatkan minat dan motivasi belajar siswa (Lagrange & Kynigos, 2014;Paseleng & Arfiyani, 2015).…”
Section: Kelebihan Dan Kelemahan Media Pembelajaran Matematika Digitalunclassified
“…Dampaknya, media ini juga mampu meningkatkan hasil belajar siswa (Lagrange & Kynigos, 2014;Moyer-Packenham & Westenskow, 2013;Nurdin et al, 2019;Paseleng & Arfiyani, 2015). Selain itu, penggunaan media ini dapat meningkatkan minat dan motivasi belajar siswa (Lagrange & Kynigos, 2014;Paseleng & Arfiyani, 2015).…”
Section: Kelebihan Dan Kelemahan Media Pembelajaran Matematika Digitalunclassified
“…Pernyataan tersebut juga disampaikan oleh Widiasworo (2017:25) yang menyatakan bahwa upaya yang dapat dilakukan oleh guru dalam menumbuhkan minat belajar siswa yaitu penggunaan media pembelajaran dalam setiap kegiatan pembelajaran serta perlunya sikap guru yang hangat dan kooperatif. Seperti halnya penelitian yang dilakukan oleh Paseleng, M. C., & Arfiyani, R (2015) dengan judul Pengimplementasian Media Pembelajaran Berbasis Multimedia Interaktif Pada Mata Pelajaran Matematika di Sekolah Dasar. Hasil dari penelitian ini dapat disimpulkan bahwa media pembelajaran berbasis multimedia interaktif memberikan pengaruh positif terhadap pembentukan minat belajar siswa khususnya pada mata pelajaran.…”
Section: Hasil Dan Pembahasan 1 Faktor Minat Belajar Matematika Siswaunclassified